¿Qué sabemos de las abejas sin aguijón (Hymenoptera: Apidae, Meliponini) en México?: Diversidad, Ecología y polinización - Baena-Díaz, Fernanda; Chévez, Estrella; Porter-Bolland, Luciana (Instituto de Ecología, A.C., 2023)
The decrease in the natural and managed populations of pollinators has placed interest on the role of pollinators, mainly in the agricultural sector, because of what is known as the "pollinator crisis". Among the most representative pollinators are bees, and within these, stingless bees (Apidae: Meliponini) are an important group. Stingless bees have great ecological, economic and cultural relevance in the world and particularly in Mexico, as a group managed for hundreds of years to obtain honey and other products from the hive. In this literature review we focus on documenting what is known about stingless bees in terms of their distribution, genetics, and ecology. Particularly, we are interested in highlighting aspects of their interactions and the ecosystem services they provide. Our objective was to synthesize the information available for Mexico and identify areas of opportunity in the study of these bees to promote better conservation and management strategies. We find that studies in this group need to be intensified to carry out an analysis of how environmental changes affects species richness, abundance, distribution, and interactions. Likewise, the lack of longitudinal studies prevents us from knowing the magnitude of the decline of these pollinators. Finally, we propose to include a social participation approach to studies of the ecology and genetics of stingless bees, which can provide very valuable information on native bees in Mexico.